Surveillance and Control Efforts for Carbapenemase-Producing Gram-Negatives at a High Burden Vietnam University Hospital. (October 2020) - Huynh, Tuan; Amber, Vasquez; Pham, Lan; Luong, Loan; Le, Tuan; Le, Khanh; Bui, Duyen; Ta, Truc; Nguyen, Dao; Trinh, Thoa; Nguyen, Yen; Bui, Diep; et al.
Abstract : Background: Carbapenem-resistant gram-negative bacteria are an urgent threat to healthcare safety around the world. In Vietnam, Although surveillance and control of multidrug-resistant organisms is a national priority, information on the burden of these resistant pathogens is still scarce. At University Medical Center Ho Chi Minh City, Vietnam, we aimed to better understand carbapenem-resistance through 2 phases: (1) assess proportion of carbapenem-resistant gram-negative organisms that are carbapanemase-producing (CP-CRO) and (2) assess transmission burden of carbapenemase-producing carbapenem-resistant Enterobacterieacea (CP-CRE) in the general intensive care unit (ICU). Methods: In the first phase, all gram-negative clinical isolates collected between November 2018 and April 2019 were tested for carbapenem-resistance using the disc-diffusion method and were defined as meropenem resistant using the Clinical and Laboratory Standards Institute 2018 break point ( M100-Performance Standards for Antimicrobial Susceptibility Testing, 28th Edition ). Carbapenem-resistant bacteria were tested for phenotypic carbapenemase-production using the Becton Dickinson Phoenix CPO Detect assay. In the second phase, we instituted CP-CRE rectal screening using CHROMagar mSuperCARBA media for all ICU patients from July through September 2019. Patients were screened on admission, and negative patients were rescreened every 2 days until discharge, death, or CRE-positive screening or culture. Admission prevalence and incidence of CP-CRE transmission was calculated among CP-CRE infected or colonized patients. Results: From November 2018 through April 2019, 599 gram-negative clinical isolates from 543 patient samples were identified. Of these, 108 were carbapenem-resistant; 107 (99%) of carbapenem-resistant isolates were carbapenemase-producing by phenotypic method. Most CP-CRO were Acinetobacter baumannii (45 of 107, 42%) or Klebsiella pneumoniae (39 of 107, 36%). During ICU CP-CRE colonization screening, the July positivity rate on admission was 40% (32 of 81), the August positivity rate on admission was 30% (21 of 71), and the September positivity rate on admission was 40% (30 of 75). Of those with negative admission screen, the proportion of new CP-CRE colonization in July was 45% (22 of 49), the proportion of new CP-CRE colonization in August was 64% (32 of 50), and the proportion of new CP-CRE colonization in September was 44% (20 of 45). Across all 3 months of screening, the proportions of CP-CRE that were Klebsiella, Citrobacter, or Enterobacter were 68% (118 of 174) and the proportion of CP-CRE that were Eschericia coli was 37% (56 of 174). The average number of days to turn from negative to positive screening result was 4.1. Conclusions: Our analysis demonstrates that nearly all carbapenem-resistant organisms at our hospital are carbapenemase producing. In the ICU, we identified a high burden of CP-CRE, attributable to high presence on admission and new acquisition in the ICU. An intervention package based on CDC-recommended enhanced infection control measures is being implemented to decrease CP-CRE transmission in the ICU. Funding: None Disclosures: None